Persistence of stigma and the cessation of substance use: comparing stigma domains between those who currently use and those who no longer use substances - Patel, Krishna; Pokorski, Emily; Norkoli, Donna; Dunkel, Emily; Wang, Xinyue; Yang, Lawrence H. (Frontiers in Psychiatry, 2024)
Introduction: Cessation of substance use, a facet of recovery, as well as mitigating stigma experienced by individuals with substance use disorder (SUD), are important to supporting health and well-being of those who use substances. But there is limited and mixed evidence on whether cessation of substance use has a positive impact on individuals’ stigma experiences. This study examined whether there were differences in stigma perceptions between those who self-report using substances and those who self-report not currently using substances associated with their SUD. Methods & materials: A survey was conducted among individuals in 10 counties of Michigan with self-identified history with SUD. The survey aimed to understand five dimensions of stigma perceptions: enacted stigma, anticipated stigma, internalized stigma, social withdrawal, and treatment stigma. Survey items for each measure were adapted from prior literature. The mean was calculated for each stigma measure for analyses. Data analyses tested whether there were significant differences in each of the five stigma domains between the two groups using either regression or t-test, depending on the necessity to include covariates. Results: Findings suggested that among the five stigma domains, only internalized stigma showed statistically significant differences between the two groups (b=0.19, se=0.08, p<0.05) after adjusting for covariates (as needed). Those who were no longer using substances had lower internalized stigma compared to those who were currently using substances associated with their SUD. Analyses suggested that the other four stigma domains, enacted stigma, anticipated stigma, social withdrawal, and treatment stigma, did not show statistically significant differences between the two groups. Discussion: While self-stigmatization (i.e., internalized stigma) was lower amongst those who report no longer using, our patterns suggest a persistence of stigma regardless of cessation of substances associated with SUD, particularly among stigma domains that are based on perceptions of how others may still perceive individuals who have used substances. Though more research is needed, results suggest that public health programmatic, policy, and campaign efforts that aim to eliminate stigma should account for and tailor to both people who report using and those who report no longer using substances to capture the breadth of needs in communities.